2016
DOI: 10.1039/c6cp02323a
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent adsorption of amino acid analogues on noble-metal nanoparticles: influence of edges and vertices

Abstract: First-principles calculations on nanoscale-sized noble metal nanoparticles demonstrate that planes, edges and vertices show different noncovalent adsorption propensities depending on the adsorbate functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 91 publications
(179 reference statements)
0
24
0
Order By: Relevance
“…In vacuo plane-wave density functional theory (PW-DFT) calculations have shown that imidazole adsorbs more strongly to the edge and vertex sites of Au NPs than to the planar Au(111) surface. 76 In contrast, this same study found benzene (the closest analogue to Tyr; phenol was not investigated in this study) to adsorb more weakly to Au NPs at both the low-coordinate Au atom sites and both facets, compared with the infinite planar surfaces.…”
Section: 38mentioning
confidence: 71%
“…In vacuo plane-wave density functional theory (PW-DFT) calculations have shown that imidazole adsorbs more strongly to the edge and vertex sites of Au NPs than to the planar Au(111) surface. 76 In contrast, this same study found benzene (the closest analogue to Tyr; phenol was not investigated in this study) to adsorb more weakly to Au NPs at both the low-coordinate Au atom sites and both facets, compared with the infinite planar surfaces.…”
Section: 38mentioning
confidence: 71%
“…[33][34][35] The vdW-DF approaches use an explicit nonlocal correlation term to describe the dispersion interactions and have been applied to a wide range of systems. 30,[36][37][38][39][40] Previously-reported lane wave density functional theory (PW-DFT) calculations using the revPBE-vdW-DF functional of the ad-sorption energies of non-covalently adsorbed molecules to noble metal interfaces have shown good agreement with experiment. [40][41][42][43][44][45][46][47] The adsorption energy of the trans isomer of AB (tAB) to Ag(111) has previously been reported, involving calculations using the revPBE-vdW-DF functional.…”
Section: Introductionmentioning
confidence: 79%
“…CYP is a group of isozymes containing the metabolism of drugs, steroids, fatty acids, bile acids, and carcinogens. The results indicate that these studied compounds are nonsubstrate and noninhibitor of CYP enzymes [ 34 ]. In terms of AMES toxicity, all the studied compounds were observed to be nontoxic.…”
Section: Resultsmentioning
confidence: 99%